Reintegration As A Pillar Of National Resilience: Failed Reintegration As A Strategic Vulnerability Exploited By Non-Traditional Security Threats In Post-Conflict Aceh - Satya Adhie Wibowo; Septiar Dwi Putra; Nefra Firdaus; Harri Dolli Hutabarat; Arifuddin Uksan (Bajang Institute, 2026)
Twenty-one years after the Helsinki Memorandum of Understanding, Aceh is routinely presented as one of Southeast Asia's most successful cases of conflict resolution. That reputation, however, rests largely on the completion of disarmament and demobilisation, while the reintegration phase remains structurally unfinished. This article argues that failed reintegration should be conceptualised not as a residual welfare problem but as a strategic vulnerability that non-traditional security actors can exploit. Employing an interpretive case study design operationalised through framework-guided document analysis, the study integrates three analytical lenses: the international DDR framework, Indonesia's national resilience doctrine (Astagatra), and defence management standards, particularly the threat–vulnerability–consequence risk model. Four vulnerability clusters are identified: fiscal-economic failure marked by elite capture and an unresolved beneficiary data deficit; exploitation by transnational criminal networks operating along the Malacca Strait corridor; intergenerational transmission of conflict memory in the absence of completed transitional justice; and political-structural uncertainty arising from the scheduled expiry of Aceh's special autonomy fund in 2027. The analysis suggests that the Aceh case extends the remobilisation literature, and the emerging research on criminal recidivism among ex-combatants, in a direction those literatures have not yet examined: economically remarginalised ex-combatants are absorbed into transnational criminal economies that require no successor armed organisation, a trajectory that conventional DDR success metrics fail to register because it produces no armed conflict data. The article develops an indicative risk matrix ranking the four clusters and derives six cross-institutional early warning indicators. It concludes that reintegration policy functions as an instrument of vulnerability reduction, analytically equivalent in importance to enforcement action against threat actors themselves